Modeling and simulation of solar PV module for comparison of two MPPT algorithms (P&O & INC) in MATLAB/Simulink - Hayder Moayad Abd Alhussain; Naseer Yasin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper introduces a procedure for the modelling of a PhotoــVoltaic (PV) cell and the application of maximum power point tracking (MPPT) in step-by-step with MATLAB/Simulink. The model of one diode is used to explore the characteristics of IــV and PــV curves of 60W PV module. Due to the non-linear and time varying of PV characteristics, the generated power of the PV is continually varying with atmospheric conditions like temperature and irradiation, the MPPT technology is very important to chase maximum power point (MPP) on the PــV curve to obtain maximum output power from PV array. This study focuses on two common types algorithms of MPPT, namely perturb and observe (P&O) and incremental conductance (INC). A DC--DC boost converter is implemented to regulate the voltage output from the PV array's and for the application of MPPT algorithm.